The Effect of Facilities, Quality, and Price on Consumer Satisfaction at Welijo Cafe and Freshmarket - Siti Kholifah; Mohammad Muklis Sulaiman (Research Trend in Technology and Management, 2024)
This study aims to examine the influence of facilities, quality, and price on consumer satisfaction in welijo café and freshmarket. This study used a sample of 97 respondents. The hypothesis testing used in this study uses validity test, reliability test, classical assumption test, determination coefficient test, multiple linear regression test, t-test, and f test. The data that has been collected is analyzed using SPSS version 25. The results of the t-test analysis showed that the facility variable (X1), quality variable (X2), and price variable (X3) had a positive influence on consumer satisfaction (Y). With the result of (X1) t count (3,054) > t table (1,985), (X2) t count (3,846) > t table (1,985), (X3) t count (2,603) > t table (1,985). The results of the F test were obtained with an F value calculated > F table (68,342 > 2.70). The test results show that facilities, quality, and price have a partial effect on consumer satisfaction at welijo cafe and freshmarket, the results of simultaneous testing of facilities, quality, and price have an effect on consumer satisfaction at welijo cafe and freshmarket. And the dominant variable that affects consumer satisfaction is quality.